Online Crowdfunding Platform Information System - Amesanggeng Pataropura (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
In the modern world, especially in the field of crowd funding, technology is getting more advanced to facilitate fundraising activities. By utilizing computer technology in the field of crowd funding, it will facilitate fundraising activities carried out by creators and providing funds by donor. Such as can be done online fundraising. Currently there are still many people who carry out manual fundraising activities which require a lot of time because they have to make documents to support fundraising and they have to approach potential donor. The possibility of losing data on donors who have provided funds is very likely because funder data is only written in a book which causes the data to become irregular. To solve the existing problem is to create a system that can store data on fundraisers and donors electronically. Computerized systems can help fundraisers (creators) and donors. This system is made with the waterfall method and uses a web base where users need an internet connection to access this system.